PERAN LPTK DALAM MENYIAPKAN TENAGA GURU SMK BIDANG AGRIBISNIS - Mukhidin, Mukhidin; Dartum, Dartum (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The role of LPTK of High School Vocational Teacher of agribusiness field should be restructured the educational system and the curriculum offerings in agribusiness field. The reforms are also needed in assessment of needs analysis and broader cooperation. The LPTK should be able to redesign the curriculum of high school vocational teacher's candidate of agribusiness field related to the needs and development of agribusiness field and should be as the facilitator and mediator on the variety of agribusiness activity for the candidate and also High School Vocational Teacher of agribusiness field. Some of the approach that should be reviewed by LPTK should refer to the analysis result of the Ministry of Agriculture is aimed to the development of curriculum design, implementation model and the evaluation. Besides that the role of LPTK need to access the agribusiness curriculum materials as outlined in the course of Agribusiness. The High School Vocational Teacher in Agribusiness fields are play the strategic roles, the especially in shaping the entrepreneurial spirit in agribusiness fields and develop a comprehensive network of agribusiness and develop the potential of learners. Thus the LPTK roles are very essential in printing the educators, particularly vocational teacher candidates' agribusiness. Keywords: Agribusiness, High School Vocational Teacher of Agribusiness Field, LPTK